Stratigraphic and sedimentological framework of the Tinrhert Plateau (Cenomanian–Turonian, SE Algeria). (June 2019) - Benyoucef, Madani; Zaoui, Djamila; Adaci, Mohammed; Ferré, Bruno; Meister, Christian; Piuz, André; El Qot, Gamal M.; Mennad, Abdelkader; Tchenar, Soumia; Bensalah, Mustapha
Abstract: The present work reviews the lithostratigraphy, biostratigraphy, and sedimentology of the Cenomanian–Turonian interval across the Tinrhert Plateau (southeastern Algeria). Five stratigraphic units, previously presented as informal units, are formally defined: the Mazoula (lower–middle Cenomanian), the Bordj Omar Driss (upper Cenomanian–lower Turonian), the In Adaoui (lower Turonian), the Ben Houilet (lower–middle Turonian), and the Takouazet (upper Turonian) formations. The Mazoula Formation consists of gypsiferous marls with a few bioclastic horizons. The Bordj Omar Driss Formation comprises three informal units: (a) the lower limestone unit composed of hard bioclastic limestones containing bivalves (mostly oysters), gastropods, and echinoids, (b) the middle limestone unit consisting of limestone, with an abundance of bivalves, gastropods, echinoids, ammonoids, and benthic foraminifers, (c) the upper limestone unit dominated by fine-grained limestones containing abundant ammonites, planktic foraminifers, and roveacrinids. The In Adaoui Formation is characterized by rich-ammonite limestone beds interbedded with yellowish-greenish marls. The Ben Houilet Formation can be subdivided informally into three units: (a) the mixed siliciclastic-carbonate unit composed of green marls interbedded with sandstones and bioclastic limestones; (b) the marly-limestone unit; (c) the gypsum and red beds unit. The Takouazet Formation is of indurated limestone beds devoid of fossils. The investigated succession is subdivided into four ammonite biozones: the Neolobites vibrayeanus, the Nigericeras gadeni, the Vascoceras cauvini, and the Pseudotissotia nigeriensis-Choffaticeras sinaiticum zones. The Cenomanian–Turonian boundary is located at the limit between the Bordj Omar Driss and In Adaoui Formations, coincident with the base of the Pseudotissotia nigeriensis-Choffaticeras sinaiticum Zone. The studied succession shows the development of a ramp depositional system in response to the early Late Cretaceous second-order sea-level rise at the southern margin of the Tethys. Sequence-stratigraphic surfaces and system tracts are identified and tracked across the Tinrhert Plateau resulting in a detailed reconstruction. Four sedimentary unconformities (SB Tin 1-4) are recognized and tracked laterally, defining three third-order depositional sequences (DS Tin 1-3).